2017
DOI: 10.1007/978-3-319-64731-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Vaccine Trials

Abstract: The Ebola epidemic that broke out in West Africa towards the end of 2013 had been brought under reasonable control by 2015. The epidemic had severely affected three countries. This case study is about a phase I/II clinical trial (testing for safety and immunogenicity) of a candidate Ebola virus vaccine in 2015 in a sub-Saharan African country which had not registered any cases of the Ebola virus disease. The study was designed as a randomized double-blinded trial. It was sponsored and funded by one of the bigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…. .. be injected with an experimental vaccine that might cause aches and fever – but could protect against the Ebola virus” (Tangwa et al, 2018). Altruism and public spirit were particularly apparent as there was no risk of contracting the virus in Canada.…”
Section: The Principle Of Risk Paritymentioning
confidence: 99%
“…. .. be injected with an experimental vaccine that might cause aches and fever – but could protect against the Ebola virus” (Tangwa et al, 2018). Altruism and public spirit were particularly apparent as there was no risk of contracting the virus in Canada.…”
Section: The Principle Of Risk Paritymentioning
confidence: 99%
“…This may sound absurd, but it is not surprising, given the continent’s history with clinical trials and research during epidemics. The 21st-century debate of ethics dumping, that is the export of unethical research practices from high-income to lower income settings, is relevant here, as an Ebola vaccine case study has previously shown (Tangwa et al, 2018).…”
Section: Vaccine Trials: Ethics Misinformation and Preparednessmentioning
confidence: 99%
“…The Ebola outbreak in West Africa saw an upsurge in health research on the Ebola virus disease. It remains unclear whether the different studies carried out at the time aligned with local needs (Tangwa et al, 2018), but Africa has made major strides in defining its research priorities for COVID-19. For example, the African Academy of Sciences (AAS) hosted a consultative webinar to discuss Africa's COVID-19 priorities and later launched an online survey with the goal of defining Africa's COVID-19 research agenda.…”
Section: Research Priority Settingmentioning
confidence: 99%
“…On the one hand, in resource-poor settings, ‘financial incentives and access to health care are a major driver for enrolment in studies’ (Mduluza et al, 2013; Mfutso-Bengo et al, 2008). On the other hand, preliminary results from a study undertaken in Canada (in relation to an Ebola vaccine) suggest that, in high-income settings, participant motivations include the desire to help develop a new vaccine, and the desire to help others (Tangwa et al, 2018).…”
Section: Carementioning
confidence: 99%